Suppression of River Ice by Thermal Effluents - Ashton ,George D (1979)
The ice suppression resulting from discharge of warm water into rivers during winter is analyzed with emphasis on two different cases. In Part 1 the case of a thermal effluent fully mixed across the flow section is analyzed to include the effects of unsteadiness in the effluent temperature and the meteorological variations. The location of the ice edge is determined either by a 0 C water temperature criterion or an equilibrium ice melting analysis. The choice of the applicable criterion emerges naturally from the analysis even though the location of the ice edge may be considerably different when a steady-state analysis is done. In Part 2 the case of a side discharge of heated effluent is analyzed, also in an unsteady manner, and the effects of transverse dispersion are included in the analysis. Comparisons are made in both Parts 1 and 2 to limited field data that are available. (Author)